Anxiety and social relationship among middle school adolescents in denpasar: a cross sectional study - Made Dian Sulistiowati (Jurnal Keperawatan, 2022)
Introduction: Mental health is a critical aspect of the adolescence period. Several symptoms, such as anxiety, loneliness, depression, sleep disturbance, and self-harming thoughts, are likely to emerge among adolescents with mental health issues. Objectives: This study aimed to explore the level of anxiety and social relationship in middle-school adolescents in Denpasar. Methods: This descriptive study enrolled a cross-sectional design. Eighty-eight middle-school adolescents in public and private junior high schools in the Denpasar City area were included as study participants. Data were collected using the Depression Anxiety Stress Scale (DASS) and social relationship questionnaire. Data analysis was conducted by univariate statistical analysis. Results: Findings revealed that 43.5% of participants were experiencing a moderate level of anxiety. The moderate anxiety responses on the physical, cognitive, psychological, and behavioral aspects were also documented. The level of social relationships was identified as moderate, high, and low, with a total percentage of 45.7%, 27.2%, and 27.2%, respectively. These social relationships were characterized by moderate responsiveness, effective communication, and responsibility. Conclusions: Many participants were experiencing a moderate level of anxiety and social relationship. Thus, their skills in constructing good social relationships and managing issues were still insufficient. We suggest organizing a program that actively engages the role of parents and schools to prevent and promote mental health awareness and issues among adolescents.